The satirical almanac "DiPiniada" as visual historical source in the study of ordinary life "displaced persons" (1946-1947) - Volodymyr Tarasov (Cхід, 2017)
The history of "displaced persons" (or DPs) is one of the major historical context of the postwar period. On the European continent, it lasts throughout the second half of the 1940s in the territory occupied by Germany, Austria and Italy. From our point of view, the study of the problem has a very strong historiographical focus, which is associated with a number of national studies.